2017
DOI: 10.1007/s11760-017-1173-9
|View full text |Cite
|
Sign up to set email alerts
|

Clustering-based quantisation for PDE-based image compression

Abstract: Finding optimal data for inpainting is a key problem in the context of partial differential equation based image compression. The data that yields the most accurate reconstruction is real-valued. Thus, quantisation models are mandatory to allow an efficient encoding. These can also be understood as challenging data clustering problems. Although clustering approaches are well suited for this kind of compression codecs, very few works actually consider them. Each pixel has a global impact on the reconstruction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…'Partial Differential Equation (PDE)' is based on an iterative approach [3,14,29], produces good results when missed regions are smaller and time consumption is more when missed regions are larger.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…'Partial Differential Equation (PDE)' is based on an iterative approach [3,14,29], produces good results when missed regions are smaller and time consumption is more when missed regions are larger.…”
Section: Related Workmentioning
confidence: 99%
“…This novel amended approach of K-means with exemplar based on the inpainting method has shown a tradeoff in subjective perception and execution time. In literature, quantization with diffusion based inpainting method [3,8,18] and PDE based method [3][4]14] has been attempted. The K-means approach has been used here for the color image quantization.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, we show that quantisation methods can also imply scale-spaces and that this leads to practical consequences for inpainting-based compression. In this application context, quantisation has so far only been the main focus in the work of Hoeltgen et al [7] who compared multiple different strategies. However, they did not consider scale-space ideas and concluded that non-uniform quantisation does not offer advantages over uniform ones in inpainting-based compression.…”
Section: Introductionmentioning
confidence: 99%
“…Transform-based image and video compression algorithms are still the preferred choice in many applications [33]. However, in recent years there has been a growing interest in alternative approaches [1,11,18,30]. It has been shown that partial differential equation (PDE)-based methods represent a viable alternative in the context of image compression.…”
Section: Introductionmentioning
confidence: 99%